Then, Brighter Teeth...Now, Better Highways - Hercules Incorporated (1947 Hercules Advertisements, 1947)
Advertisement for Vinsol Resin manufactured and sold by the Hercules Powder Company for use in cement and road construction. The advertisement details the varied uses of naval stores past and present, highlighting Hercules' discovery and development of new products and uses. This advertisement appeared in the June 1947 issue of Naval Stores Review. Formed in 1912 as part of an anti-trust settlement with DuPont, the Hercules Powder Company (later Hercules Inc.) initially specialized in the manufacture of explosives and smokeless powders and subsequently diversified its business to encompass a variety of industrial products, including pine and paper chemicals, synthetics, pigments, polymers, and cellulose.
Keywords: Chemical industry; Research, Industrial; Hercules Incorporated; Corporations; Naval stores; Gums and resins; Advertising, Industrial